Prenatal antibiotic use and risk of childhood wheeze/asthma: A meta‐analysis. Issue 8 (6th August 2015) - Zhao, Desheng; Su, Hong; Cheng, Jian; Wang, Xu; Xie, Mingyu; Li, Kesheng; Wen, Liying; Yang, Huihui
Abstract: Background: Existing body of knowledge suggests that antibiotic use during pregnancy was inconsistently associated with childhood wheeze/asthma. The aim of this study was to determine whether exposure to antibiotic during pregnancy could increase the risk for childhood wheeze/asthma using a comprehensive meta‐analysis. Methods: PubMed, MEDLINE, and China National Knowledge Infrastructure (CNKI) were systematically searched for studies up to September 10, 2014, and additional studies were found by searching reference lists of relevant articles. For this meta‐analysis, cohort studies and case–control studies assessing the association between antibiotic use during pregnancy and risk of childhood wheeze/asthma were included. Extracted data were mainly pooled using random‐effects model. Study quality was assessed using the Newcastle–Ottawa Quality Assessment Scale (NOS). Results: Ten studies were identified in final analysis. Pooling analysis of these studies showed an OR of 1.20 (95% CI, 1.13–1.27) for wheeze/asthma. After excluding case–control studies and prospective studies without achieving high scores on the NOS, the pooled OR was 1.18 (95% CI, 1.11–1.26). We found the risk of antibiotic use and pooled ORs of wheeze/asthma were 1.09 (95% CI, 0.92–1.29) for the first trimester, 1.14 (95% CI, 1.01–1.29) for the second trimester, and 1.33 (95% CI, 1.11–1.60) for the third trimester, respectively. Conclusions: This meta‐analysis suggests that antibiotic exposure during pregnancy may increase the risk of wheeze/asthma in childhood. Besides, the risk of developing wheeze/asthma in childhood was marked during last two trimesters of pregnancy. Future studies of large‐size and prospective cohorts which adequately address concerns for confounder bias are needed to examine the relationship between antibiotic use and risk of childhood asthma. Abstract :